1997
DOI: 10.1177/036354659702500317
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Muscle Firing Patterns During the Windmill Softball Pitch

Abstract: The purpose of this study was to describe the activity of eight shoulder muscles during the windmill fast-pitch softball throw. Ten collegiate female pitchers were analyzed with intramuscular electromyography, high-speed cinematography, and motion analysis. The supraspinatus muscle fired maximally during arm elevation from the 6 to 3 o'clock position phase, centralizing the humeral head within the glenoid. The posterior deltoid and teres minor muscles acted maximally from the 3 to 12 o'clock position phase to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
85
2
5

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 13 publications
2
85
2
5
Order By: Relevance
“…The resulting internal rotation velocity was over 4,000°/sec which, although smaller than overhand pitching, is a high magnitude (Table 1). Maffett et a1 (15) observed high levels of activity for the pectoralis major and subscap ularis, contributing to adduction and internal rotation of the humerus during windmill pitching.…”
Section: Figure 5 Forces (% Body Weight) Applied To the A N At The Smentioning
confidence: 97%
See 2 more Smart Citations
“…The resulting internal rotation velocity was over 4,000°/sec which, although smaller than overhand pitching, is a high magnitude (Table 1). Maffett et a1 (15) observed high levels of activity for the pectoralis major and subscap ularis, contributing to adduction and internal rotation of the humerus during windmill pitching.…”
Section: Figure 5 Forces (% Body Weight) Applied To the A N At The Smentioning
confidence: 97%
“…The diagnosis of bicipital tendinitis is often made with little consideration to the possibility of subscapularis or pectoralis strain, which may occur as increased shoulder extension is followed by large forces and torques produced during the delivery motion (Figures 3 and 5). Maffett et al (15) concluded that the high levels of activity for the pectoralis major and subscapularis observed during early delivery also contribute to the stabilization of the anterior capsule of the shoulder. Despite the possibility of injury to these structures, pain in the anterior shoulder is often treated by injection of a steroid/analgesic mixture into the bicipital tendon area.…”
Section: Figure 5 Forces (% Body Weight) Applied To the A N At The Smentioning
confidence: 99%
See 1 more Smart Citation
“…Despite increasing participation in fast-pitch among young women, historically little research has been done on the windmill pitching style. Initially, the consensus was that injury potential was low because the motion appeared seemingly effortless (2)(3)(4)(5)(6). Although recent literature suggests that overuse injuries are prevalent, controversy regarding this matter still exists.…”
Section: Introductionmentioning
confidence: 99%
“…Existing research has primarily focused on elite pitchers, illustrating that the forces produced with the windmill motion are similar to the overhand throw (3,5). Based on this correlation with the overhand throw, studies of baseball pitchers' delivery were investigated.…”
Section: Introductionmentioning
confidence: 99%